Measurement of the Poisson expansion effect on crack openings in self-sensing concrete - Xueying Wang; Lee Scott Cunningham; Michele Win Tai Mak; Janet Lees; Abir Al-Tabbaa; Stuart Kenneth Haigh (Scientific Reports)
Abstract Concrete infrastructure tends to degrade with extended service life, but detecting deterioration with conventional inspection methods can be challenging. Existing approaches such as developing self-sensing concrete by adding electrically conductive fillers to the cement matrix often suffer from high costs and complex manufacturing processes for casting the concrete from fresh. This study looks beyond the commonly discussed resistance-based and capacitance-based self-sensing mechanisms in the elastic deformation regime of the concrete and investigates the changes in electrical conductivity due to micro-crack opening through Poisson expansion by utilising the measurement technique of drilling the concrete to insert conductive epoxy for electrode embedment to achieve intrinsic self-sensing on as-built regular concrete (i.e. without conductive fillers). Experimental results on existing plain concrete samples showed a good correlation between the compressive load and the fractional change in resistivity (FCR). Finite element analysis (FEA) was then used to further investigate the effect of changes in conductivity in the direction of loading and orthogonal directions on the measured electrical behaviour of the concrete. Results showed that the correlation between the FCR and the compressive load depends on the relationship between the load-parallel and -orthogonal gauge factors. Beyond a threshold level, the electrical signal picked up by the electrodes reflects the material’s behaviour in the direction orthogonal to the loading direction due to Poisson expansion. Further numerical simulation has suggested that to achieve a stable measurement, the electrodes’ penetration should equal the spacing.